Saccharomyces cerevisiae and Dekkera bruxellensis interactions in alcoholic fermentations: growth and 4-ethylphenol production - Coutinho, Rute (2014)
The yeast Dekkera/Brettanomyces bruxellensis can cause enormous economic losses both in wine industry and fuel-ethanol processes due to production of phenolic off-flavour compounds and low ethanol productivities. In winemaking this microbial hazard is usually tackled by the use of chemical preservatives such as sulphur dioxide. In spite of this, D. bruxellensis strains are frequently found in wines at low levels (ca 103 cells/ml) where they can metabolise residual sugars producing phenolic off-flavours compounds, such as 4-ethyl phenol. In the present work we investigated S. cerevisiae and D. bruxellensis interactions during alcoholic fermentations and evaluated the effectiveness of antimicrobial peptides secreted by S. cerevisiae to prevent growth of the main wine spoilage yeast and the production of 4-ethylphenol. Several fermentations were performed with single cultures of D. bruxellensis and mixed cultures of S. cerevisiae and D. bruxellensis, both in synthetic grape juice (SGJ) and grape must. Yeast growth (culturability and viability) and fermentation performance (i.e. sugars consumption, ethanol and 4-ethylphenol production) of those fermentations was accessed by different methods, namely by florescence in situ hybridization and flow cytometry. Results showed that S. cerevisiae significantly reduced the growth of D. bruxellensis and the production of 4-ethylphenol both in SGJ and grape must fermentations performed with mixed cultures. Moreover, our work also showed that antimicrobial peptides secreted by S. cerevisiae are effective to prevent growth of D. bruxellensis and production of phenolic off-flavor compounds in wine.